Workshop Perancangan Projek Penguatan Profil Pelajar Pancasila (P5) Bagi Guru SD Negeri di Kabupaten Mahakam Ulu - Maria Melani Ika Susanti (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2026)
The implementation of Merdeka Curriculum in education units requires teachers as the spearhead of the implementation of learning in the classroom to really understand the concept and how it is implemented in schools. Unfortunately, not all teachers get the same opportunity to understand the conceptual ins and outs of Merdeka Curriculum. This case is experienced by most public elementary school teachers in Mahakam Ulu Regency who do not have a full understanding of Merdeka Curriculum and other concepts that follow it. The purpose of this community service activity is to provide opportunities for elementary school teachers in Mahakam Ulu Regency to better understand the Pancasila Student Profile Strengthening Project (P5) which is an integral part of the implementation of Merdeka Curriculum through collaboration with fellow teachers. Teachers who do not have an optimal understanding of P5 are invited to thoroughly explore the concept and implementation of P5 in the education unit. Teachers learn to recognize the school's potential in depth through SWOT analysis and then practice with groups to select P5 topics and determine project activity planning for P5. The results of each group's planning were shared and given input by other groups and facilitators.